CT colonography followed by elective surgery in patients with acute diverticulitis: a radiological-pathological correlation study - Flor, Nicola (Abdom Radiol (NY), 2020)
PURPOSE: To perform a radiologic-pathologic correlation analysis of sigmoid colon in patients undergoing pre-operative CT Colonography (CTC) after an episode of acute diverticulitis (AD). METHODS: Fifty-nine consecutive patients (31/28 M/F; 58 ± 13 years) underwent CTC 55 ± 18 days after AD, 8 ± 4 weeks before surgery. Thirty-seven patients (63%) underwent conventional abdominal CT at time of AD. An experienced blinded radiologist retrospectively analyzed all images: disease severity was graded according to the Ambrosetti classification on conventional CT and according to the diverticular disease severity score (DDSS) on CTC. A GI pathologist performed a dedicated analysis, evaluating the presence of acute and chronic inflammation, and fibrosis, using 0–3 point scale for each variable. RESULTS: Of 59 patients, 41 (69%) had at least one previous AD episode; twenty-six patients (44%) had a complicated AD. DDSS was mild-moderate in 34/59 (58%), and severe in 25/59 (42%). All patients had chronic inflammation, while 90% had low-to-severe fibrosis. Patients with moderate/severe fibrosis were older than those with no/mild fibrosis (61 ± 13 versus 54 ± 13). We found a significant correlation between DDSS and chronic inflammation (p = 0.004), as well as DDSS and fibrosis (p = 0.005). Furthermore, fibrosis was correlated with complicated acute diverticulitis (p = 0.0.27), and with age (p = 0.067). At multivariate analysis, complicated diverticulitis was the best predictor of fibrosis (odds ratio 4.4). Patient age and DDSS were other independent predictors. CONCLUSION: DDSS-based assessment on preoperative CTC was a good predictor of chronic colonic inflammation and fibrosis. In addition, the presence of complicated diverticulitis on CT during the acute episode was most predictive of fibrosis.